1D Nanowire Heterojunction Electrocatalysts of MnCo2O4/GDY for Efficient Overall Water Splitting. (4th December 2021) - Qi, Lu; Zheng, Zhiqiang; Xing, Chengyu; Wang, Zhongqiang; Luan, Xiaoyu; Xue, Yurui; He, Feng; Li, Yuliang
Abstract: Rational design and synthesis of non‐precious metal‐based electrocatalysts for efficient overall water splitting (OWS) in an integrated electrolyzer are of great significance for the development of hydrogen energy. To this end, nanowire‐structured heterogenous MnCo2 O4 /graphdiyne arrays are synthesized on the surface of 3D carbon cloth (NW‐MnCo2 O4 /GDY) by using in situ assembly and coupling strategy. Experiments demonstrated that the special core/shell‐nanowire structure and synergistic interaction between the MnCo2 O4 and GDY can greatly improve the electric conductivity, facilitate the mass/ion transport and gas emissions, expose more active sites, and thus lead to the enhancement of the catalytic activity and long‐term stability of the electrocatalysts for OWS. For example, the alkaline water electrolyzer assembled by NW‐MnCo2 O4 /GDY shows high‐performance with only 1.47 and 1.60 V required to reach a current density of 10 and 100 mA cm −2, respectively, which is even better than that of previously reported electrocatalysts. Abstract : The outstanding properties of GDY provide wide design space for the design and synthesis of 1D nanowire heterojunction electrocatalysts with excellent catalytic activity and long‐term stability for oxygen‐evolution reaction, hydrogen‐evolution reaction, as well as overall water splitting in alkaline conditions. Interestingly, the NW‐ MnCo2 O4 @GDY based alkaline electrolyzer needs a small cell voltage of 1.60 V to reach 100 mA cm −2 .